Prostatic Artery Embolization for Benign Prostatic Hyperplasia: Anatomical Aspects and Radiation Considerations from a Case Series of 210 Patients - Mohamed Shaker; Essam Hashem; Ahmed Abdelrahman; Ahmed Okba (The Arab Journal of Interventional Radiology, 2021)
Context Prostatic artery embolization (PAE) has been established as a safe and effective treatment option for symptomatic benign prostatic hyperplasia (BPH). Thorough knowledge of detailed prostatic artery (PA) anatomy is essential. Aims The aim of this study was to provide a pictorial review of PA anatomy and prevalence of related anatomical variants, in addition to other anatomical and radiation dose considerations. Settings and Design Case series and review of literature. Materials and Methods We performed PAE for 210 patients from November 2015 to November 2020 under local anesthesia only. Anatomy, procedure duration, fluoroscopy time, radiation dose, technical success, and complications were analyzed. Statistical Analysis Used Descriptive statistics were analyzed using Microsoft Excel software. Results A total of 210 patients (420 sides) were analyzed. Double arterial supply on the same side was noted in 12 patients (5.7%). In 10 patients (4.7%), only a unilateral PA was identified. In two patients (0.9%), no PA could be identified. Frequencies of PA origins were calculated. Penile, rectal, and vesical anastomoses were identified with 79 (18.8%), 54 (12.9%), and 41 (9.8%) of PAs, respectively. Median skin radiation dose, procedure time, and fluoroscopy time were 505 mGy, 73 and 38 minutes, respectively. Complications occurred in nine patients (4.3%), none of them was major. Conclusions Knowledge of PA anatomy is essential when treating BPH by PAE for optimum results. There is no enough evidence to support routine use of preoperative computed tomography angiography and intraoperative cone-beam computed tomography as means of improving safety or efficacy.